Soluble syndecans: biomarkers for diseases and therapeutic options. (23rd July 2018) - Bertrand, Jessica; Bollmann, Miriam
Abstract : Syndecans are important mediators of signalling by transmitting external stimuli into the cells. This role in signal transduction has been attributed mainly to the membrane‐bound syndecans. In the last years, however, the soluble ectodomain of syndecans generated by shedding has come into the focus of research as this process has been show to modulate the syndecan‐dependent signalling pathways, as well as other pathways. This review summarizes the current knowledge about the induction of syndecan shedding and the different pathways modulated by shed syndecan proteins. This review summarizes the known and putative sheddases for each syndecan and describes the exemplary conditions of sheddase activity for some syndecans. This review summarizes the proposed use of shed syndecans as biomarkers for various diseases, as the shedding process of syndecans depends crucially on tissue‐ and disease‐specific activation of the sheddases. Furthermore, the potential use of soluble syndecans as a therapeutic option is discussed, on the basis of the current literature. Linked Articles: This article is part of a themed section on Translating the Matrix. To view the other articles in this section visithttp://onlinelibrary.wiley.com/doi/10.1111/bph.v176.1/issuetoc